The loss of stability analyses of an elastic and viscoelastic composite circular plate in the framework of three-dimensional linearized theory - Kutug, Z; Yahnioglu, N; Akbarov, SD (ELSEVIER, 2003)
In the present paper, in the framework of three-dimensional linearized theory of stability (TDLTS) the statement of the problem of stability loss of a circular plate made from a viscoelastic composite material is suggested. The method for solution to these problems is developed by employing Laplace transform and FEM. It is assumed that the plate has an insignificant initial rotationally symmetrical imperfection. Stability is assumed to be lost when the imperfection starts to increase and grow indefinitely. Numerical results obtained by TDLTS are compared with corresponding results obtained in the framework of the third order refined plate theory. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: circular plate; critical time; finite element method; stability loss; viscoelastic composite; Mechanics